Konsep Karakter Kepemimpinan Nabi Ibrahim AS Dalam Membentuk SDM Unggulan Perspektif Al-Qur’an - Hidayatullah (Al-Wasathiyah: Journal of Islamic Studies, 2022)
This article describes the concept of the leadership character of Prophet Ibrahim as the superior character of leaders and a reference for empowering Human Resources (HR) in the perspective of the Qur'an. The research was conducted using a library research approach with the maudhu'i interpretation method (thematic interpretation). Among the leadership characters of Prophet Ibrahim in this study are mastering interpersonal communication skills, strategists, argumentative, exemplary, religious, peace-loving, and responsibility. These characters are obtained based on historical studies between Prophet Ibrahim and his father, his people, King Namrudz, Prophet Lut, King of Egypt, mysterious guests and his son (Ismail) which were adapted from his story in the Qur'an. These leadership characters are expected to serve as role models for today's leaders in implementing their leadership according to Ibrahim's prophetic leadership guidelines in the contemporary context in Indonesia. Be it in the context of personal relationships with individual families, local communities, community leaders and so on. Thus, this research is expected to contribute to the development of the concept of prophetic character for office holders at all levels of life.